Pertanggungjawaban PT KAI Commuter Indonesia terhadap Kerugian Penumpang Akibat Gangguan Operasional KRL Jabodetabek - Kuranii, Kelvin Akhmad; Adhan S, Sepriyadi; Ramadhan, Harsa Wahyu; Zazili, Ahmad; Mustika, Dora (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Public transportation has become a basic need of the community in mobilizing. For every transportation process, passengers are required to have a ticket as proof of travel documents. Passengers and carriers are bound by the existence of a contract of carriage, which is a contract of carriage that gives birth to a legal relationship and gives rise to rights and obligations. This research aims to determine the civil liability of PT KAI Commuter Indonesia is based on an operational disruption event that caused an accident that occurred while transporting passengers. This study uses a normative juridical research method that is descriptive with a qualitative approach. The type of data used is primary data obtained from laws and regulations and secondary data sources obtained from literature materials. The data collection method uses literature studies and direct interviews as supporting data in processing data to produce conclusions regarding legal protection for consumers in legal events in the form of operational disruptions to the EMU Jabodetabek Commuter Line. The results of the study show that passengers and carriers have the right and obligation to get safety guarantees, as well as PT KAI Commuter Indonesia is responsible for losses suffered by passengers in the form of ticket refunds and compensation for accident victims, whether they are dead, disabled, or injured. The compensation paid by PT KAI Commuter Indonesia is a premium paid by passengers managed by the insurance company, namely PT Jasa Raharja. However, in practice, it is still unclear in the laws and regulations and also the scope in the agreement with the insurance company.